Pelaksanaan Fungsi Legislasi DPRD dalam Pembuatan Peraturan Daerah Kabupaten Sijunjung Tahun 2018 - Lara Kharisma; Jumiati Jumiati (Jurusan Ilmu Administrasi Negara, 2022)
This research is motivated by problems that occur in the implementation of the function of the DPRD as a regional regulation maker which is considered to be still not optimally carried out, such as many DPRDs not using their initiative rights optimally, there are still many problems in the preparation of academic texts for making regional regulations, there are still disagreements between DPRD and the community and many others that the authors met related to the legislative function of the DPRD in 2018. This study aims to determine the implementation of the legislative function of the Sijunjung Regency DPRD in making the 2018 Sijunjung Regency regional regulations as well as the obstacles and efforts in implementing the legislative function. This research was conducted and processed using a qualitative descriptive approach, while the data collection techniques were carried out through interviews and documentation studies. Based on the results of research and discussion, it was found that the implementation of the legislative function of the Sijunjung Regency DPRD in making regional regulations for Sijunjung Regency in 2018 was still considered less than optimal, this was evidenced in the use of the initiative rights of the Sijunjung Regency DPRD, which was still minimal, as seen from 19 draft regional regulations, only 4 designs came from the initiative. DPRD. Furthermore, there are also obstacles in the implementation of the legislative function of the DPRD which come from internal in the form of facilities and infrastructure, human resources and budgets and externally in the form of the environment around the organization and political culture. To overcome these obstacles, efforts can be made that also come from internal and external organizations and are considered to be resolved properly.